Rationale and design of the MULTISTARS AMI Trial: A randomized comparison of immediate versus staged complete revascularization in patients with ST-segment elevation myocardial infarction and multivessel disease - Stähli, Barbara E.; Varbella, Ferdinando; Schwarz, Bettina; Nordbeck, Peter; Felix, Stephan B.; Lang, Irene M.; Toma, Aurel; Moccetti, Marco; Valina, Christian; Vercellino, Matteo; Rigopoulos, Angelos G.; Rohla, Miklos; et al. (American Heart Journal, 2020)
About half of patients with acute ST-segment elevation myocardial infarction (STEMI) present with multivessel coronary artery disease (MVD). Recent evidence supports complete revascularization in these patients. However, optimal timing of non-culprit lesion revascularization in STEMI patients is unknown because dedicated randomized trials on this topic are lacking. Study design: The MULTISTARS AMI trial is a prospective, international, multicenter, randomized, two-arm, open-label study planning to enroll at least 840 patients. It is designed to investigate whether immediate complete revascularization is non-inferior to staged (within 19-45 days) complete revascularization in patients in stable hemodynamic conditions presenting with STEMI and MVD and undergoing primary percutaneous coronary intervention (PCI). After successful primary PCI of the culprit artery, patients are randomized in a 1:1 ratio to immediate or staged complete revascularization. The primary endpoint is a composite of all-cause death, non-fatal myocardial infarction, ischemia-driven revascularization, hospitalization for heart failure, and stroke at 1 year. Conclusions: The MULTISTARS AMI trial tests the hypothesis that immediate complete revascularization is non-inferior to staged complete revascularization in stable patients with STEMI and MVD.
CRIS-Team Scopus Importer:2020-09-04